A novel instrument for ascorbic acid detection based on the eddy current principle for oranges (Citrus x sinensis), pineapples (Ananas comosus), and bilimbi (Averrhoa bilimbi) - Shahibul Fadhli; Muhammad Syukri Surbakti; Khairi Suhud; Zakaria Husen; Ahmad Fairuz Omar; Sidratun Ulfa Sari (Jurnal Natural, 2026)
Ascorbic acid, a water-soluble vitamin, is prone to degradation during the storage of fruits and vegetables, necessitating fast and reliable detection techniques for quality control. This study presents a digital instrument employing the eddy current principle for the sensor, designed with a slit-structured copper (Cu) electrode coated with a TiO₂ nanocomposite, to quantify ascorbic acid levels in orange, pineapple, and bilimbi juice. The system incorporates an Arduino Uno microcontroller and an inductive proximity sensor to monitor voltage shifts induced by interactions between ascorbic acid molecules and the electrode surface. Calibration was carried out using standard solutions ranging from 1 to 9 ppm, with UV-Vis spectrophotometry serving as the validation method. The sensor exhibited a strong linear correlation (R² = 0.991), with output voltage decreasing from 6.12 V at 1 ppm to 4.86 V at 9 ppm. Measured concentrations were 8.93 ppm (orange), 7.07 ppm (pineapple), and 4.59 ppm (bilimbi), closely aligning with UV-Vis results. The mean relative error was 3.25%, indicating an accuracy of 96.74%. Statistical analysis using linear regression and the t-test confirmed no significant difference from the reference method. These results highlight the sensor's potential as a rapid and precise tool for ascorbic acid detection in the agri-food industry.